Pseudechis guttatus venom proteome: Insights into evolution and toxin clustering - Viala, Vincent L.; Hildebrand, Diana; Trusch, Maria; Arni, Raghuvir K. [UNESP]; Pimenta, Daniel C.; Schlueter, Hartmut; Betzel, Christian; Spencer, Patrick J. (Elsevier B.V., 2014)
The Australian Elapidae spotted black snake Pseudechis guttatus venom proteome composition was analyzed by high throughput mass spectrometry. The crude venom proteins were decomplexed by 2D-PAGE and in-gel digestion peptides from 66 spot samples and analyzed by tandem mass spectrometry-LC-ESI-ion trap. Protein identification was performed combining PEAKS studio 7.0 and Mascot software. The analysis identified L-amino-acid oxidases, phospholipases A2, metalloproteases, nerve growth factors and ecto-5'-nucleotidases, and for the first time in this venom the components cysteine-rich secretory proteins similar to pseudechetoxin, phospholipase B and transferrin-like protein. The envenomation symptoms are in agreement with the identified components, but the present limitations of database information might impair the detection of toxin families, protein species and still unknown toxins. From the qualitative point of view, the similarity of this venom with the ones from other Pseudechis species could be assigned to recent speciation events.Biological significanceStudies on the proteome of Australian Elapidae (Ancanthophiinae) are quite rare. In the present work we performed, using classic proteomic methods, a qualitative and partial analysis of the proteic components of Pseudechis guttatus venom. Although previous studies contributed to the knowledge of the major components of this venom, our study revealed some yet undescribed protein species, as well as new toxins, such as CRiSPs, phospholipase B, transferrin-like protein and ecto 5'-nucleotidase. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Pseudechis guttatus; Elapidae; Toxins; High throughput; Proteomics; 2D-PAGE